Bioinspired Continuum Robots with Programmable Stiffness by Harnessing Phase Change Materials. Issue 6 (3rd February 2023) - Zhang, Jie; Wang, Bo; Chen, Haohan; Bai, Jianing; Wu, Zhigang; Liu, Ji; Peng, Haijun; Wu, Jianing
Abstract: Continuum robots offer significant advantages over traditional ones in some specific scenarios, such as urban search and rescue, minimally invasive surgery, and inspection of cluttered environments. However, motions and/or operations of existing continuum robots always suffer from those limitations in varying curvature interaction scenarios because of the homogeneity and singleness of the structural stiffness. Herein, inspired by the mechanism of an elephant trunk for regulating local stiffness, a three‐segment continuum robot constructed by tensegrity structure, which relies on a stiffness tunable material, with its Young's modulus switchable between 1.79 and 271.62 MPa to achieve the robotic stiffness programmable characteristics, is proposed. For predicting the robotic configuration with varying stiffness distribution, a mechanical model based on the framework of the finite element method is derived. Theoretical predictions reveal that the curvature of each segment can be regulated by programming stiffness of the smart materials; therefore, the customizable design can offer an effective route for real‐time robotic interactions. By evaluating motion characteristics, stiffness performance, and conformal interaction capability, the experimental results demonstrate that the robot can freely regulate the configuration on‐demand, which may provide a foundation for the application of continuum robots with programmable stiffness for interacting with unstructured environments. Abstract : Inspired by the mechanism of an elephant trunk for regulating local stiffness, a three‐segment continuum robot constructed by a class‐3 tensegrity structure is proposed, which relies on a stiffness tunable material to achieve the robotic stiffness programmable characteristics. This study may provide a foundation for the potential application of continuum robots for interacting with unstructured environments.